2014
DOI: 10.1097/mpg.0000000000000489
|View full text |Cite
|
Sign up to set email alerts
|

Points to Be Considered When Applying FibroScan S Probe in Children With Biliary Atresia

Abstract: Objectives:With the introduction of smaller probes (S1, S2), the use of transient elastography has been expanded to children. Accordingly, we aimed to address points of consideration in probe choice and interpretation of measured liver stiffness by applying and comparing FibroScan S and M probes in biliary atresia.Methods:Using S1, S2, and M probes, 3 liver stiffness measurements, success rates, and interquartile ranges were obtained from 100 patients. Patients were assigned to 2 groups according to thoracic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…Recently, 2D-SWE accuracy was evaluated in children post liver transplantation [21]. Other studies analyzed the influence of some technical parameters on measurement reliability such as: type of probe used, place and depth of measurement [15,22]. Tutar et al [23] showed that although liver fibrosis can be assessed using 2D-SWE in children, differentiation of mild to moderate fibrosis stages (F1, F2) could not be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, 2D-SWE accuracy was evaluated in children post liver transplantation [21]. Other studies analyzed the influence of some technical parameters on measurement reliability such as: type of probe used, place and depth of measurement [15,22]. Tutar et al [23] showed that although liver fibrosis can be assessed using 2D-SWE in children, differentiation of mild to moderate fibrosis stages (F1, F2) could not be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The paediatric S probes can improve reliability in this regard. A recent study [22] aimed at addressing points of consideration in the probe choice and interpretation of measured LS by comparing FibroScan S1, S2 and M probes in children with biliary atresia. The authors concluded that the S1 probe is more appropriate for use in small children, especially those with a thorax perimeter of <45 cm, but if no S probe is available, the M probe may be acceptable in children whose thorax perimeter is >45 cm [22].…”
Section: Discussionmentioning
confidence: 99%
“…The S probes (S1 and S2) use a pulse-tracking frequency of 5 MHz at window depths of 15–40 mm and 20–50 mm, respectively [21]. The M probe uses a pulse-tracking frequency of 3.5 MHz at a window depth of 20–60 mm, and the XL probe uses a lower pulse-tracking frequency of 2.5 MHz at a window depth of 35–75 mm [19, 22].…”
Section: Ultrasound-based Dynamic Elastographymentioning
confidence: 99%
“…It has been shown that LSM decreased with probe size (S1 < S2 < M) and caution is needed when interpreting the results [52].…”
Section: Te In Healthy Childrenmentioning
confidence: 99%